Development of Electrochemical DNA Biosensor Based on 30 nm Gold Nanoparticle Modified Electrode by Electro Less Deposition for HPV 18 - Nur Syahen Koo Siew Kim (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To develop an improved technique by using the 30 nm size of gold nanoparticles (AuNPs) attached to a single-stranded DNA probe for the detection of HPV18. To prepare HPV 18 probe-conjugated AuNPs which the gold nanoparticle is labelled as HPV 18. To examine the performance of the functionalized AuNPs based IDE device for DNA of HPV 18 detection based on electrical measurement of DNA hybridization using dielectric analyzer.